How the consumer confidence index could increase air travel demand forecast accuracy? - Teyssier, Narjesse (Cranfield University, 2012)
Because of the complex nature of the air transportation industry with continuous changes in the environment, the past records of air traffic forecasters, either using trend extrapolation or causal models or even more sophisticated methods have not produced accurate results. In recent years, the trend has been to develop air travel demand forecasts based on econometric equations, which specify a relationship between passenger traffic and a number of traditional key economic variables. However these forecasts do not take into account air traffic downturns or strong increases. Periods of economic or political uncertainty are associated with consumer confidence volatility, suggesting that swings in confidence could influence air travel demand. The failure of forecasters to predict the repeated peaks and troughs since 2001 has renewed interest in supplementing econometric forecasts with qualitative indicators such as consumer confidence indices. These variables are available for some countries and the aim of this research is to find whether forecasts based on these indices are more accurate in predicting short-term traffic up and downs. Through the analysis of three case studies, this thesis examines how the introduction of a confidence index in the air travel demand model, including only macroeconomic variables, could have some ability to improve the forecast accuracy of the model. For each case study, the demand for the market has been divided according to the existing supply side segments, namely legacy carriers, low cost carriers and non-scheduled airlines. The results show that this confidence index has some ability to improve the forecast accuracy of both, the global top-down and the bottom-up models built for some supply side segments, notably the legacy ones during periods of uncertainty such as 1991, 2001, 2008 and 2009. The results are also suggesting that the forecasting power of this index is increasing when applied to more mature markets such as the demand linked to the US legacy carriers or to the European charter airlines.This study is appraising the performance of consumer confidence indexes by examining their impact on different air travel demand forecasts.